Contaminants Inputs at Alambari river, São José dos Campos city, São Paulo State, Brazil - Lee, Isabella Gumiero [UNESP] (2021)
This paper describes a hydrochemical study held at Alambari river, which crosses the installations of Henrique Lage refinery (Revap), São José dos Campos city, São Paulo State, Brazil. The hydrochemical characterization of the Alambari river waters allowed to assess its quality and verify the presence of domestic and/or industrial effluents and other environmental impacts caused by urbanization and refinery activities. Physicochemical parameters, inorganic compounds, heavy metals, total dissolved solids, dissolved radon, and BTEX were analyzed in rainwater and 32 water samples collected at Alambari river which provided a robust dataset for this study. The water samples exhibited similar hydrochemical pattern, except in one case that yielded discrepant values for most of the analyzed parameters. This monitoring point indicated excessive contribution of domestic effluents as evidenced by its high content of surfactants and also of sewage effluents, as pointed out by its higher concentration of chloride and nitrate. Piper’s diagram highlighted that the hydrochemical facies of rainwater and surface water are bicarbonate sodic. Gibbs boomerang diagrams suggest the dominant influence of rainwater dilution effects on the hydrochemical composition of the Alambari river waters. It was not possible identify that the refinery affects the water quality in relation to the parameters analyzed, but the possibility of contamination by other compounds or contamination of soil and sediments is not ruled out.